TGFβ receptor inhibition unleashes interferon-β production by tumor-associated macrophages and enhances radiotherapy efficacy. Issue 3 (17th March 2022) - Hamon, Pauline; Gerbé De Thoré, Marine; Classe, Marion; Signolle, Nicolas; Liu, Winchygn; Bawa, Olivia; Meziani, Lydia; Clémenson, Céline; Milliat, Fabien; Deutsch, Eric; Mondini, Michele
Abstract : Background: Transforming growth factor-beta (TGFβ) can limit the efficacy of cancer treatments, including radiotherapy (RT), by inducing an immunosuppressive tumor environment. The association of TGFβ with impaired T cell infiltration and antitumor immunity is known, but the mechanisms by which TGFβ participates in immune cell exclusion and limits the efficacy of antitumor therapies warrant further investigations. Methods: We used the clinically relevant TGFβ receptor 2 (TGFβR2)-neutralizing antibody MT1 and the small molecule TGFβR1 inhibitor LY3200882 and evaluated their efficacy in combination with RT against murine orthotopic models of head and neck and lung cancer. Results: We demonstrated that TGFβ pathway inhibition strongly increased the efficacy of RT. TGFβR2 antibody upregulated interferon beta expression in tumor-associated macrophages within the irradiated tumors and favored T cell infiltration at the periphery and within the core of the tumor lesions. We highlighted that both the antitumor efficacy and the increased lymphocyte infiltration observed with the combination of MT1 and RT were dependent on type I interferon signaling. Conclusions: These data shed new light on the role of TGFβ in limiting the efficacy of RT, identifying a novel mechanism involving the inhibition of macrophage-derived type I interferon production, and fostering the use of TGFβR inhibition in combination with RT in therapeutic strategies for the management of head and neck and lung cancer.